(untitled) (American Journal of Interdisciplinary Research and Innovation, 2023)
The term “gas flaring” is referred as a combustion system that burns associated, or liquids and gases that are being released in excess during unplanned or normal operations that are over pressuring in numerous industrial procedures, including landfills, refineries, coal industry, chemical companies, and gas extraction. Gas flaring contributes greatly to greenhouse gas emissions. It generates heat, noise, and makes the environment uninhabitable. Oporoma Community is the administrative center of Southern Ijaw Local Government Area (SILGA), Bayelsa State, Niger Delta region. One of the Communities in the region of Niger Delta that produce oil is Oporoma, and its being used as a case study. The primary data was obtained through an interview with about one hundred and fifty (150) persons (both men and women) between the age of 18 - 90 years. 50 persons from the age groups of 18 – 30, 31 – 50, and 51 – 90 years which focused mainly on harmful impact of gas flaring on human health, and its environment. Every investigation and data that were gotten from Oporoma community has negative human health and environmental effect, because of burning of gas. This gas flaring practice has caused poverty to many people in the community with health, environmental, and economic challenges. The government and policy makers in the Niger Delta region of Nigeria are also contributing to the negative impacts of gas flaring on local communities and the environment. The challenges faced by people living in areas where gas is being flared, such as air pollution, water contamination, and soil degradation, are strong arguments for ending this practice. Companies that are failing to properly process the gases produced during oil extraction should be heavily fined. Instead of being wasted through flaring, these gases could be used to produce cooking and domestic gas, as well as electricity. It is time for gas flaring to be brought to an end, particularly in the Oporoma community of the Niger Delta.